Effects of rhamnolipids on the cell surface characteristics of Sphingomonas sp. GY2B and the biodegradation of phenanthrene. Issue 39 (4th May 2017) - Lin, Weijia; Liu, Shasha; Tong, Le; Zhang, Yumei; Yang, Jing; Liu, Weiting; Guo, Chuling; Xie, Yingying; Lu, Guining; Dang, Zhi
Abstract : The mechanism of the interaction of rhamnolipids on strain GY2B. Abstract : A number of biosurfactants have been applied in the bioremediation of contaminated environment; however, their impact on bioremediation is controversial. The present study was focused on the effects of biosurfactants on the biodegradation capability and the interaction of biosurfactants with bacterial cells. The impacts of the widely used biosurfactant rhamnolipids on a typical phenanthrene-degrading Sphingomonas sp. GY2B were examined. It was observed that the removal percentages of phenanthrene decreased when rhamnolipids were added in higher than 1 critical micelle concentration (CMC); however, no difference in the removal percentages was observed after 24 h treatment when the rhamnolipids were added in lower than 1 CMC. This may be due to the fact that higher concentrations (above 1 CMC) of rhamnolipids cause the sequestration of PAHs into surfactant micelles. This phenomenon was further confirmed by the results of FTIR analysis. SEM images and the zeta potential test further proved that the addition of rhamnolipids decreased the cell surface hydrophobicity (CSH) and reduced the amount of filamentary materials. The ratio of saturated fatty acids to unsaturated fatty acids (sat/unsat) of cells showed a decreasing trend from 38.50 to 26.10 in the absence of rhamnolipids. However, no obvious difference was observed with 1 CMC of rhamnolipids (35.34 and 33.77 at 24 h and 48 h, respectively), indicating that rhamnolipids may not enhance the membrane fluidity and transmembrane transport of phenanthrene. Overall, the addition of rhamnolipids in a concentration above its CMC could cause a lag period in the biodegradation of phenanthrene. Therefore, it is necessary to determine the optimal dosage of the biosurfactants to enhance the surfactant-amended remediation applications involving the biodegradation of PAHs.